Bedah Karya Poster Desain untuk Difabel Menggunakan Teori Semiotika - Sari Wulandari (Bina Nusantara University, 2013)
Year of 2011 was a special year for the people of Indonesia with ASEAN ParaGames held in Solo on December 12th to December 20th. Solo held ASEAN Paralympic Games in 2011 in the month of December. These special moments were used by Aikon Media, ADGI (Asosisasi Graphic Designers Indonesia), and DKV BINUS to organize a poster exhibition with works by students and lecturers of DKV BINUS University, DKV UNS Solo and Solo ADGI chapter called